(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
This study looks at how soil chemical characteristics are affected by the magnetization of saline irrigation water from Almasab Alam. The dirt was gathered from the research location and put into pots that were completely identical to one another. Onion plants were sown in the soil, with three replications done for each case to determine the average results. Different types of irrigation water were used to irrigate the anvils. Seven different methods of testing the irrigation water were used, including irrigating with river water, irrigating with salty Almasab Alam drainage water without magnetization, and irrigating with magnetized Almasab Alam water with intensities (7000, 5000, 3000, 2000, and 1000) gauss. The highest decrease of the three important elements that nourish the plant: netrate, phosfate, and potasum, was found in the case of irrigation with magnetized water with an intensity of 3000 gauss. The highest percentage decrease in all chemical properties occurred when using magnetized water with strength of 3000 gauss.Utilizing magnetic technology, provides appropriate water for irrigating crops by Almasab Alam water, and overcoming the investigation location’s water scarcity.